The use of local concentrated heat versus topical acyclovir for a herpes labialis outbreak: results of a pilot study under real life conditions - Wohlrab J; Voß F; Müller C; Brenn LC (Dove Medical Press, 2013)
Johannes Wohlrab,1 Franziska Voß,2 Christian Müller,2 Lars C Brenn21Department of Dermatology and Venereology, Martin Luther University of Halle-Wittenberg, Halle, 2Department of Medical Science and Operations, Riemser Pharma GmbH, Greifswald, GermanyBackground: Frequent outbreak of herpes labialis can affect quality of life by prodromes like burning, itching, and swelling. Topical applied preparations aim to shorten the duration of symptoms, inhibit the virus replication and/or accelerate the healing process. Local concentrated heat (LCH) can reduce burning, itching, or swelling of the skin by influence of mechano-heat sensitive afferent neurons.Patients and methods: To examine the effectiveness of two different topical applications (LCH versus topical acyclovir [TACV]) under real life conditions, we conducted a prospective, observational, reference-controlled cohort pilot study with 103 patients. Occurrence of prodromal burning, itching, swelling, and quality of life were assessed.Results: The LCH observation group (OG) showed a significantly faster improvement in all symptoms after 1-day of application than the TACV OG. The burden and duration of disease was lower and shorter in the LCH OG than in the TACV OG.Conclusions: The prodromal symptoms in recurrent herpes labialis were attenuated more effectively by LCH than by TACV.Keywords: herpes labialis, local concentrated heat, acyclovir